(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: The consumer’s culture determines his behavior in a certain direction and not others. Because the culture that was formed by him as a result of customs, traditions, experiences, and others is a major driver towards sales. Materials and Methods: The questionnaire was used as a main tool for collecting the required data by distributing it to the sample members. The researcher distributed the questionnaire realistically to the clients of the city center of Hilla, and no form was excluded, so that the final sample size was (384) clients, and it was analyzed using a number of statistical tests available within the two programs. Statisticians (AMOS.V.23, SPSS.v23). Results: The results of the study show that there is a correlation of some dimensions of the intermediate variable with the dependent variable, and there is an effect relationship for some dimensions of the intermediate variable with the dependent one Conclusion: The consumer culture is the first line of defense to protect the consumer from the risks of poor goods and services and commercial fraud.